(untitled) (Journal of Face Aesthetics, 2024)
The planning of orthodontic treatment involves not only defining desired tooth movements to achieve a proper bite but, above all, predicting the impact of these actions on the soft facial tissues. The position of teeth, especially in the front part of the upper and lower jaw, determines the support of the lips, whose harmonious arrangement is a significant factor determining facial aesthetics. The case of a patient is presented in this work, who was diagnosed with a deficiency of space for the correct alignment of teeth, excessive protrusion and inclination of incisor teeth, increased tension of the muscles around the mouth, and chin during lip closure. After a thorough analysis of diagnostic data, it was decided to undergo orthodontic treatment combined with the extraction of 4 premolars, which, after 28 months, led to achieving proper occlusal conditions and a significant improvement in the aesthetics and function of the soft tissues of the facial profile.